(untitled) (The Agriculturists, 2015)
The present study was undertaken to assess the impacts of rice-prawn gher (RPG) system on farm productivity, food security and poverty reduction in Bangladesh. In this study, farm survey data, extracted from a comprehensive questionnaire from two study villages viz. Bilpabla (RPG farming) and Chanchra (year-round modern varietyYRMV) located in Khulna and Jessore district, respectively were analyzed deliberately. This study consists of a random selection of ninety farmers from Bilpabla Village and one-hundred farmers from Chanchra. The study indicates that RPG farming system has significant impacts on farm productivity. On an average, yield of modern variety (MV) was reasonably higher in RPG farming system than that of YRMV farming system. In addition, the households engaged in RPG farming system (Bilpabla Village) have simultaneously generated more household income and per capita income (more than twice), relative to YRMV farming system (Chanchra Village). Moreover, the households of Bilpabla are superior to those households residing in Chanchra in terms of physical, social and economic access (purchasing power) which permits them to acquire and consume well-balanced food as well as sufficient calorie intake. Therefore, the RPG farming system had significant impacts on food security and poverty reduction. The Agriculturists 2014; 12(2) 126-136